Product Life Cycle (Siklus Hidup Produk) pada Tanaman Anggrek di DD Orchid Nursery - Fikien, Agnes; Agustim, Warter (Journal of Indonesian Economic Research, 2023)
This fieldwork practice activity (PKL) was carried out by conducting research on Product Life Cycle (product life cycle) on orchid plants at DD Orchid Nursery, this activity aims to see how much influence Product Life Cycle (product life cycle) on the marketing of orchid plants at DD Orchid Nursery. Data collection is done by observation, interviews, and documentation. The results show the Product Life Cycle process. This Industry is still not optimal enough, which affects product sales in each period, so it is necessary to improve strategies to find out the quantity of Product Life Cycle (product life cycle) that will be successful and can estimate the type of Product Life Cycle (product life cycle). which will be able to compete in the market in the future, and increase the amount of production than usual so that stock remains available. So that customer demand is always met and does not reduce the number of products to be offered, and can meet sales targets. Penelitian ini dilaksanakan dengan melakukan penelitian tentang Product Life Cycle (Siklus hidup produk) pada tanaman anggrek di DD Orchid Nursery, kegiatan ini bertujuan untuk melihat seberapa besar pengaruh Product Life Cycle (Siklus hidup produk) terhadap pemasaran tanaman anggrek di DD Orchid Nursery. Pengumpulan data dilakukan dengan cara observasi, wawancara dan dokumentasi. Hasilnya menunjukkan bahwa proses Product Life Cycle (Siklus hidup produk) pada industri ini masih belum cukup maksimal, yang berpengaruh terhadap penjualan produk di setiap periodenya, sehingga perlu adanya peningkatan strategi untuk mengetahui kuantitas Product Life Cycle (Siklus hidup produk) yang akan berhasil, dan dapat memperkirakan jenis Product Life Cycle (Siklus hidup produk) yang kiranya dapat bersaing di pasaran masa mendatang, serta menambah jumlah produksi dari biasanya agar stock tetap tersedia. Sehingga permintaan pelanggan selalu terpenuhi dan tidak mengurangi jumlah product yang akan ditawarkan, serta dapat memenuhi target penjualan.